2021
DOI: 10.5114/aoms/119782
|View full text |Cite
|
Sign up to set email alerts
|

“Pulmonary dysfunction in children with Duchenne muscular dystrophy may appear earlier than we thought – analysis using novel methodology based on z-scores."

Abstract: IntroductionRespiratory status is one of the main factors affecting the length of survival in patients with Duchenne muscular dystrophy (DMD) – the most common, severe, progressive muscular dystrophy.The aim: (1) to assess pulmonary function in DMD patients using the z-score method and (2) to identify factors affecting it, irrespective of the disease progress.Material and methodsWe evaluated 55 boys (aged 5 – 18 years) with DMD. The spirometry was performed with: forced vital capacity (FVC), forced expiratory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Many studies have shown that respiratory function declines at a rate of 6-11% annually in patients with DMD [1,6,7]. A major component of respiratory dysfunction seems to be a decline in inspiratory muscle strength [6,8].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that respiratory function declines at a rate of 6-11% annually in patients with DMD [1,6,7]. A major component of respiratory dysfunction seems to be a decline in inspiratory muscle strength [6,8].…”
Section: Introductionmentioning
confidence: 99%
“…Innovative forms of lung function monitoring at home are extremely important during the COVID-19 pandemic, especially for patients with chronic diseases and dysfunction of the respiratory system. Many studies showed that respiratory function declines at a rate of 6-11% annually in patients with DMD [3][4][5]. Moreover, respiratory muscle weakness leads to secondary changes, such as decreased lung compliance, ineffective cough with deterioration of airway clearance, and repeated infections [3,4], which causes DMD patients to have a higher risk of a severe course of COVID-19 [7].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies showed that respiratory function declines at a rate of 6-11% annually in patients with DMD [3][4][5]. Moreover, respiratory muscle weakness leads to secondary changes, such as decreased lung compliance, ineffective cough with deterioration of airway clearance, and repeated infections [3,4], which causes DMD patients to have a higher risk of a severe course of COVID-19 [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that pulmonary function declines at a rate of 6-11% annually in patients with DMD [3][4][5]. Moreover, respiratory muscle weakness leads to secondary changes such as decreased lung compliance, ineffective cough with deterioration of airway clearance, and repeated infections [6,7].…”
Section: Introductionmentioning
confidence: 99%